Hadith #114 - Sahih al-Bukhari - Ubaidullah bin 'Abdullah bin 'Umar Ø¹Ø¨ÙØ¯ Ø§ÙÙÙ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø¹ÙØ± Ø¨Ù Ø§ÙØ®Ø·Ø§Ø¨ (Sahih al-Bukhari)
Ibn `Abbas said, âWhen the ailment of the Prophet (ï·º) became worse, he said, âBring for me (writing) paper and I will write for you a statement after which you will not go astray.â But `Umar said, âThe Prophet is seriously ill, and we have got Allahâs Book with us and that is sufficient for us.â But the companions of the Prophet (ï·º) differed about this and there was a hue and cry. On that the Prophet (ï·º) said to them, âGo away (and leave me alone). It is not right that you sh
Grade: Sahih

Hadith #1490 - Sahih al-Bukhari - Ubaidullah bin 'Abdullah bin 'Umar Ø¹Ø¨ÙØ¯ Ø§ÙÙÙ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø¹ÙØ± Ø¨Ù Ø§ÙØ®Ø·Ø§Ø¨ (Sahih al-Bukhari)
Ibn `Abbasâ said, âUsama rode behind Allahâs Messenger (ï·º) from `Arafat to Al-Muzdalifa; and then Al-Fadl rode behind Allahâs Messenger (ï·º) from Al-Muzdalifa to Mina.â Ibn `Abbas added, âBoth of them said, âThe Prophet kept on reciting Talbiya till he did the Rami of Jamrat-Al-`Aqaba.â â
Grade: Sahih

Hadith #1626 - Sahih al-Bukhari - Ubaidullah bin 'Abdullah bin 'Umar Ø¹Ø¨ÙØ¯ Ø§ÙÙÙ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø¹ÙØ± Ø¨Ù Ø§ÙØ®Ø·Ø§Ø¨ (Sahih al-Bukhari)
Ibn `Abbas said, âUsama bin Zaid rode behind the Prophet (ï·º) from `Arafat to Al-Muzdalifa; and then from Al-Muzdalifa to Mina, Al-Fadl rode behind him.â He added, âBoth of them (Usama and Al-Fadl) said, âThe Prophet (ï·º) was constantly reciting Talbiya till he did Rami of the Jamarat-Al-`Aqaba.â
Grade: Sahih

Hadith #3538 - Sahih al-Bukhari - Ubaidullah bin 'Abdullah bin 'Umar Ø¹Ø¨ÙØ¯ Ø§ÙÙÙ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø¹ÙØ± Ø¨Ù Ø§ÙØ®Ø·Ø§Ø¨ (Sahih al-Bukhari)
Al-Miswar bin Makhrama and `Abdur-Rahman bin Al-Aswad bin âAbu Yaghuth said (to me), âWhat forbids you to talk to `Uthman about his brother Al-Walid because people have talked much about him?â So I went to `Uthman and when he went out for prayer I said (to him), âI have something to say to you and it is a piece of advice for you â `Uthman said, âO man, from you.â (`Umar said: I see that he said, âI seek Refuge with Allah from you.â) So I left him and went to them. Then the mess
Grade: Sahih

Hadith #3709 - Sahih al-Bukhari - Ubaidullah bin 'Abdullah bin 'Umar Ø¹Ø¨ÙØ¯ Ø§ÙÙÙ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø¹ÙØ± Ø¨Ù Ø§ÙØ®Ø·Ø§Ø¨ (Sahih al-Bukhari)
That Al-Miswar bin Makhrama and `Abdur-Rahman bin Al-Aswad bin âAbu Yaghuth had said to him, âWhat prevents you from speaking to your uncle `Uthman regarding his brother Al-Walid bin `Uqba?â The people were speaking against the latter for what he had done. âUbaidullah said, âSo I kept waiting for `Uthman, and when he went out for the prayer, I said to him, âI have got something to say to you as a piece of advice.â `Uthman said, âO man! I seek Refuge with Allah from you. So I went
Grade: Sahih

Hadith #3764 - Sahih al-Bukhari - Ubaidullah bin 'Abdullah bin 'Umar Ø¹Ø¨ÙØ¯ Ø§ÙÙÙ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø¹ÙØ± Ø¨Ù Ø§ÙØ®Ø·Ø§Ø¨ (Sahih al-Bukhari)
I went to `Uthman. After reciting Tashah-hud, he said,. âThen after no doubt, Allah sent Muhammad with the Truth, and I was amongst those who responded to the Call of Allah and His Prophet and believed in the message of Muhammad. Then took part in the two migrations. I became the son-in-law of Allahâs Messenger (ï·º) and gave the pledge of allegiance to him By Allah, I never disobeyed him, nor did I deceive him till Allah took him unto Him.â
Grade: Sahih

Hadith #3852 - Sahih al-Bukhari - Ubaidullah bin 'Abdullah bin 'Umar Ø¹Ø¨ÙØ¯ Ø§ÙÙÙ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø¹ÙØ± Ø¨Ù Ø§ÙØ®Ø·Ø§Ø¨ (Sahih al-Bukhari)
That Al-Miqdad bin `Amr Al-Kindi, who was an ally of Bani Zuhra and one of those who fought the battle of Badr together with Allahâs Messenger (ï·º) told him that he said to Allahâs Messenger (ï·º), âSuppose I met one of the infidels and we fought, and he struck one of my hands with his sword and cut it off and then took refuge in a tree and said, âI surrender to Allah (i.e. I have become a Muslim),â could I kill him, O Allahâs Messenger (ï·º), after he had said this?â Allahâs Me
Grade: Sahih

Hadith #4238 - Sahih al-Bukhari - Ubaidullah bin 'Abdullah bin 'Umar Ø¹Ø¨ÙØ¯ Ø§ÙÙÙ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø¹ÙØ± Ø¨Ù Ø§ÙØ®Ø·Ø§Ø¨ (Sahih al-Bukhari)
Ibn `Abbas said, âWhen Allahâs Messenger (ï·º) was on his deathbed and there were some men in the house, he said, âCome near, I will write for you something after which you will not go astray.â Some of them ( i.e. his companions) said, âAllahâs Messenger (ï·º) is seriously ill and you have the (Holy) Qurâan. Allahâs Book is sufficient for us.â So the people in the house differed and started disputing. Some of them said, âGive him writing material so that he may write for you
Grade: Sahih

Hadith #5691 - Sahih al-Bukhari - Ubaidullah bin 'Abdullah bin 'Umar Ø¹Ø¨ÙØ¯ Ø§ÙÙÙ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø¹ÙØ± Ø¨Ù Ø§ÙØ®Ø·Ø§Ø¨ (Sahih al-Bukhari)
that `Umar bin Nafi` told him that Nafi`, Maula `Abdullah had heard `Umar saying, âI heard Allahâs Apostle forbidding Al-Qazaâ.â âUbaidullah added: I said, âWhat is Al-Qazaâ?â âUbaidullah pointed (towards his head) to show us and added, âNafi` said, âIt is when a boy has his head shaved leaving a tuft of hair here and a tuft of hair there.â Ubaidullah pointed towards his forehead and the sides of his head. âUbaidullah was asked, âDoes this apply to both girls and boys
Grade: Sahih

Hadith #7237 - Sahih al-Bukhari - Ubaidullah bin 'Abdullah bin 'Umar Ø¹Ø¨ÙØ¯ Ø§ÙÙÙ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø¹ÙØ± Ø¨Ù Ø§ÙØ®Ø·Ø§Ø¨ (Sahih al-Bukhari)
`Abdullah bin `Abbas said, âO the group of Muslims! How can you ask the people of the Scriptures about anything while your Book which Allah has revealed to your Prophet contains the most recent news from Allah and is pure and not distorted? Allah has told you that the people of the Scriptures have changed some of Allahâs Books and distorted it and wrote something with their own hands and said, âThis is from Allah, so as to have a minor gain for it. Wonât the knowledge that has come to yo
Grade: Sahih

Hadith #328 - Sunan al-Nasa'i - al-Husain bin Hryth Ø§ÙØØ³ÙÙ Ø¨Ù ØØ±ÙØ«; al-Walid bin Kathir al-Makhzumi Ø§ÙÙÙÙØ¯ Ø¨Ù ÙØ«ÙØ± Ø§ÙÙØ®Ø²ÙÙÙ; Hammad bin Usamah ØÙØ§Ø¯ Ø¨Ù Ø£Ø³Ø§ÙØ© - Ø£Ø¨Ù Ø£Ø³Ø§ÙØ©; ibn Umar; Muhammad bin Ja'far bin al-Zubair ÙØÙØ¯ Ø¨Ù Ø¬Ø¹ÙØ± Ø¨Ù Ø§ÙØ²Ø¨ÙØ± Ø¨Ù Ø§ÙØ¹ÙØ§Ù; Ubaidullah bin 'Abdullah bin 'Umar Ø¹Ø¨ÙØ¯ Ø§ÙÙÙ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø¹ÙØ± Ø¨Ù Ø§ÙØ®Ø·Ø§Ø¨ (Sunan al-Nasa'i)
âI passed by the Prophet (ï·º) when he was performing Wuduâ from the well of Budaâah. I said: âAre you performing Wuduâ from it when garbage is thrown into it?â He said: âWater is not made impure by anything.'â
Grade:

Hadith #1451 - Sunan al-Nasa'i - Abdullah bin Wahb Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù ÙÙØ¨ Ø¨Ù ÙØ³ÙÙ Ø§ÙÙØ±Ø´Ù; al-Zuhri Ø§Ø¨Ù Ø´ÙØ§Ø¨ Ø§ÙØ²ÙØ±Ùâ, ÙØÙØ¯ Ø¨Ù ÙØ³ÙÙ; ibn Umar; Muhammad bin Salmah ÙØÙØ¯ Ø¨Ù Ø³ÙÙØ© Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø§ÙØ¨Ø§ÙÙÙ; Ubaidullah bin 'Abdullah bin 'Umar Ø¹Ø¨ÙØ¯ Ø§ÙÙÙ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø¹ÙØ± Ø¨Ù Ø§ÙØ®Ø·Ø§Ø¨; Yonus bin Yazid bin Abi al-Nijad ÙÙÙØ³ Ø¨Ù ÙØ²ÙØ¯ Ø¨Ù Ø£Ø¨Ù Ø§ÙÙØ¬Ø§Ø¯ (Sunan al-Nasa'i)
âThe Messenger of Allah (ï·º) led us in prayer in Mina, two rakâahs, when the people were greater in number and more secure.â
Grade:

Hadith #2659 - Sunan al-Nasa'i - Abdullah bin Wahb Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù ÙÙØ¨ Ø¨Ù ÙØ³ÙÙ Ø§ÙÙØ±Ø´Ù; al-Zuhri Ø§Ø¨Ù Ø´ÙØ§Ø¨ Ø§ÙØ²ÙØ±Ùâ, ÙØÙØ¯ Ø¨Ù ÙØ³ÙÙ; ibn Umar; Ubaidullah bin 'Abdullah bin 'Umar Ø¹Ø¨ÙØ¯ Ø§ÙÙÙ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø¹ÙØ± Ø¨Ù Ø§ÙØ®Ø·Ø§Ø¨; Yonus bin Yazid bin Abi al-Nijad ÙÙÙØ³ Ø¨Ù ÙØ²ÙØ¯ Ø¨Ù Ø£Ø¨Ù Ø§ÙÙØ¬Ø§Ø¯ (Sunan al-Nasa'i)
the Messenger of Allah designated Dhul-Hulaifah as the Miqat for the people of Al-Madinah Al-Juhfah for the people of Najd, and Yalmlam for the people of Yemen. He said: âThey are for them, and for anyone who comes to them from elsewhere. If a personâs place of residence is within the boundary of the Miqat, then (he should enter into Ihram) from where he starts his journey, and this also applies to the people of Makkah.â(Sihah)
Grade:

Hadith #2750 - Sunan al-Nasa'i - Hashaym bin Bashayr bin al-Qasim ÙØ´ÙÙ Ø¨Ù Ø¨Ø´ÙØ± Ø¨Ù Ø§ÙÙØ§Ø³Ù; ibn Umar; Ja'far bin Iyas; Ubaidullah bin 'Abdullah bin 'Umar Ø¹Ø¨ÙØ¯ Ø§ÙÙÙ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø¹ÙØ± Ø¨Ù Ø§ÙØ®Ø·Ø§Ø¨; Ya'qub bin Ibrahim bin Sa'd ÙØ¹ÙÙØ¨ Ø¨Ù Ø¥Ø¨Ø±Ø§ÙÙÙ Ø¨Ù Ø³Ø¹Ø¯ Ø¨Ù Ø¥Ø¨Ø±Ø§ÙÙÙ (Sunan al-Nasa'i)
âI was with âAli when the Messenger of Allah appointed him as governor of Yemen. When âAli came to the Messenger of Allah, âAli said: âI found that Fatimah had perfumed the house with perfume.â He said: âI tried to avoid it, and she said to me: what is the matter with you? The messenger of Allah told his Companions to exit Ihram.â He said: âI said: I have entered Ihram for that for which the Prophet entered Ihram.ââ He said: âSo I went to the Prophet and he said to me: â
Grade:

Hadith #67 - Jami' al-Tirmidhi - Abdah bin Sulaiman al-Klabi Ø¹Ø¨Ø¯Ø© Ø¨Ù Ø³ÙÙÙØ§Ù Ø§ÙÙÙØ§Ø¨Ù Ø£Ø¨Ù ÙØÙØ¯ Ø§ÙÙÙÙÙ; Hanad bin al-Sari bin Mus'ab ÙÙØ§Ø¯ Ø¨Ù Ø§ÙØ³Ø±Ù Ø¨Ù ÙØµØ¹Ø¨; Ibn Ishaq ÙØÙØ¯ Ø¨Ù Ø¥Ø³ØØ§Ù Ø¨Ù ÙØ³Ø§Ø±â; ibn Umar; Muhammad bin Ja'far bin al-Zubair ÙØÙØ¯ Ø¨Ù Ø¬Ø¹ÙØ± Ø¨Ù Ø§ÙØ²Ø¨ÙØ± Ø¨Ù Ø§ÙØ¹ÙØ§Ù; Ubaidullah bin 'Abdullah bin 'Umar Ø¹Ø¨ÙØ¯ Ø§ÙÙÙ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø¹ÙØ± Ø¨Ù Ø§ÙØ®Ø·Ø§Ø¨ (Jami' al-Tirmidhi)
âI heard AlIahâs Messenger while he was being asked about water in open areas of the land, and predators and beasts come to it.â He said: âSo Allahâs Messenger said: âWhen the water is two Qullah it does not carry filth.'â
Grade:

Hadith #557 - Sunan Ibn Majah - Abdur Rahman bin 'Abdul Malik bin Shayb Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙÙ Ø¨Ù Ø´ÙØ¨Ø©; Ibn Ishaq ÙØÙØ¯ Ø¨Ù Ø¥Ø³ØØ§Ù Ø¨Ù ÙØ³Ø§Ø±â; ibn Umar; Muhammad bin Ja'far bin al-Zubair ÙØÙØ¯ Ø¨Ù Ø¬Ø¹ÙØ± Ø¨Ù Ø§ÙØ²Ø¨ÙØ± Ø¨Ù Ø§ÙØ¹ÙØ§Ù; Ubaidullah bin 'Abdullah bin 'Umar Ø¹Ø¨ÙØ¯ Ø§ÙÙÙ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø¹ÙØ± Ø¨Ù Ø§ÙØ®Ø·Ø§Ø¨; Yazid bin Harun ÙØ²ÙØ¯ Ø¨Ù ÙØ§Ø±ÙÙ (Sunan Ibn Majah)
It was narrated from Abu Hurairah that for the Subh prayer on Fridays, the Messenger of Allah (ï·º) used to recite âAlif-Lam-Mimâ. The revelationâ¦â and âHas there not been over manâ¦â
Grade:

Hadith #558 - Sunan Ibn Majah - Abdullah bin Mubarak Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø§ÙÙØ¨Ø§Ø±Ù; Amr bin Rafa'i al-Advi. Client Of 'Umar Ø¹ÙØ±Ù Ø¨Ù Ø±Ø§ÙØ¹ Ø§ÙØ¹Ø¯ÙÙ; Ibn Ishaq ÙØÙØ¯ Ø¨Ù Ø¥Ø³ØØ§Ù Ø¨Ù ÙØ³Ø§Ø±â; ibn Umar; Muhammad bin Ja'far bin Abi Kathir ÙØÙØ¯ Ø¨Ù Ø¬Ø¹ÙØ± Ø¨Ù Ø£Ø¨Ù ÙØ«ÙØ±; Ubaidullah bin 'Abdullah bin 'Umar Ø¹Ø¨ÙØ¯ Ø§ÙÙÙ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø¹ÙØ± Ø¨Ù Ø§ÙØ®Ø·Ø§Ø¨ (Sunan Ibn Majah)
It was narrated from âAbdullah bin Masâud that for the Subh prayer on Fridays, the Messenger of Allah (ï·º) used to recite âAlif-Lam-Mim. The revelationâ¦â and âHas there not been over man..â
Grade:

Hadith #559 - Sunan Ibn Majah - Ali bin Muhammad bin Ishaq al-Tanafasi Ø¹ÙÙ Ø¨Ù ÙØÙØ¯ Ø¨Ù Ø¥Ø³ØØ§Ù Ø§ÙØ·ÙØ§ÙØ³Ù; Asim bin al-Mndhr bin al-Zubair Ø¹Ø§ØµÙ Ø¨Ù Ø§ÙÙÙØ°Ø± Ø¨Ù Ø§ÙØ²Ø¨ÙØ± Ø¨Ù Ø§ÙØ¹ÙØ§Ù; Hammad bin Salama ØÙØ§Ø¯ Ø¨Ù Ø³ÙÙØ©; ibn Umar; Ubaidullah bin 'Abdullah bin 'Umar Ø¹Ø¨ÙØ¯ Ø§ÙÙÙ Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙÙÙ Ø¨Ù Ø¹ÙØ± Ø¨Ù Ø§ÙØ®Ø·Ø§Ø¨; Waki' bin al-Jarrah ÙÙÙØ¹ Ø¨Ù Ø§ÙØ¬Ø±Ø§Ø (Sunan Ibn Majah)
âI asked Abu Saâeed Al-Khudri about the prayer of the Messenger of Allah (ï·º). He said: âThere is nothing good in that for you.â* I said: âExplain it, may Allah have mercy on you.â He said: âThe Iqamah would be given for the Zuhr prayer for the Messenger of Allah (ï·º), then one of us would go out to Al- Baqiâ, relieve himself, then come back and perform ablution, and he would find the Messenger of Allah (ï·º) still in the first Rakâah of Zuhr.ââ
Grade: